2021
DOI: 10.1210/clinem/dgab240
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Thermal Ablation in the Treatment of Primary Hyperparathyroidism: A Multicenter Study

Abstract: Purpose To evaluate the effectiveness and safety of thermal ablation for primary hyperparathyroidism (pHPT). Materials and Methods From January 2015 to March 2020, data pertaining to patients who received thermal ablation for pHPT at 4 centers were retrospectively analyzed. The median follow-up duration was 18.1months (IQR: 6.5-42.2 months). A cure referred to the reestablishment of normal values of serum calcium and intact p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…After 6-12 months of follow-up, two patients failed to show normal PTH or calcium levels. A multicenter study reported that the 7 out of 114 patients had recurrent PHPT during a follow-up period of 18.1 months ( 20 ). They found that a maximum diameter less than 0.6 cm resulted in missed ablation.…”
Section: Discussionmentioning
confidence: 99%
“…After 6-12 months of follow-up, two patients failed to show normal PTH or calcium levels. A multicenter study reported that the 7 out of 114 patients had recurrent PHPT during a follow-up period of 18.1 months ( 20 ). They found that a maximum diameter less than 0.6 cm resulted in missed ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Complications include hoarseness, hypocalcemia, perioral and limb numbness, convulsions, subcutaneous edema, various degrees of pain, cough, skin burns, hematoma, infection, and life-threatening complications during or after RFA [ 18 34 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since US-guided RFA was first used successfully in 2002 by Hänsler et al [ 17 ]. as a treatment for single parathyroid adenoma in humans, RFA has emerged as a novel method for managing PHPT [ 16 18 19 ]. However, to the best of our knowledge, no prospective studies have reported on patients who underwent RFA for PHPT.…”
Section: Introductionmentioning
confidence: 99%
“…Although thermal ablation has provided promising outcomes in PHPT treatment, a majority of the studies have a small patient number and a short follow‐up term thus yielding limited definitive evidence on the effectiveness of this method. Yet, in a recent multicenter study, thermal ablation (MWA and RFA) has been demonstrated as an effective and reliable method in PHPT treatment 10 …”
mentioning
confidence: 99%
“…Yet, in a recent multicenter study, thermal ablation (MWA and RFA) has been demonstrated as an effective and reliable method in PHPT treatment. 10 In the current issue of Journal of Clinical Ultrasound: Sonography and other Imaging Techniques, Ebrahiminik H et al have reported a retrospective study incorporating data from 27 patients with single parathyroid adenoma who were treated using ultrasound-guided RFA. 11 The study included patients diagnosed with parathyroid adenoma based on clinical, laboratory, and imaging findings who have refused undergoing surgery.…”
mentioning
confidence: 99%